1999
DOI: 10.1177/01939459922043820
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Social Support, and Sense of Coherence

Abstract: In the Salutogenic Model, Aaron Antonovsky suggested that a sense of coherence (SOC) is the key determinant in the maintenance of health. He theorized that individuals with a strong SOC have the ability to (a) define life events as less stressful (comprehensibility), (b) mobilize resources to deal with encountered stressors (manageability), and (c) possess the motivation, desire, and commitment to cope (meaningfulness). To determine the effects of SOC on health outcomes, a greater understanding of the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
94
2
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 18 publications
16
94
2
4
Order By: Relevance
“…Skärsäter, Langius, Ågren, Häggströmand Dencker (30) showed that social support is an important cornerstone in the restoration of a person's sense of coherence. Wolff and Ratner (31) found that stress and traumatic events were found to be inversely related to SOC, and social support was positively related, which is in line with the present findings of the study. Langeland and Wahl (32) observed that while social support predicted change in sense of coherence, mental symptoms did not.…”
Section: Discussionsupporting
confidence: 92%
“…Skärsäter, Langius, Ågren, Häggströmand Dencker (30) showed that social support is an important cornerstone in the restoration of a person's sense of coherence. Wolff and Ratner (31) found that stress and traumatic events were found to be inversely related to SOC, and social support was positively related, which is in line with the present findings of the study. Langeland and Wahl (32) observed that while social support predicted change in sense of coherence, mental symptoms did not.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, social support had a positive effect on SOC (Larsson & Kallenberg 1996;Wolff & Ratner 1999). In brief, previous studies suggest that both sociodemographic and health factors contribute to SOC.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Women with a history of childhood sexual abuse had a weak SOC (15). Traumatic events experienced in childhood predicted SOC more strongly than if experienced in adulthood (16).…”
Section: Introductionmentioning
confidence: 96%